2020
DOI: 10.1155/2020/7496182
|View full text |Cite
|
Sign up to set email alerts
|

“Covering Effects” under Diurnal Temperature Variations in Arid and Semiarid Areas

Abstract: Covering effects" dominated by water vapor migration in arid and semiarid areas threaten the stability of engineering entities. To explore the "covering effects" dominated by water vapor migration under the influence of diurnal temperature variations, a series of one-side evaporation experiments were conducted. Characteristics of water vapor migration between the unsaturated loess soil column with and without a lid were compared in detail to illustrate the "covering effects" on water vapor migration, as were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The research results showed that a thin ice layer appeared in the cold end with the impermeable layer, and the frost susceptibility increased with the increased initial moisture content and fine contents. Liu et al (2020) found that "soil lid" and the "soil covering effects" existed in both loess soil columns with and without lids under cyclic diurnal temperature variation [28] . The "soil covering effects" for the soil column with a lid were much more obvious.…”
Section: Introductionmentioning
confidence: 99%
“…The research results showed that a thin ice layer appeared in the cold end with the impermeable layer, and the frost susceptibility increased with the increased initial moisture content and fine contents. Liu et al (2020) found that "soil lid" and the "soil covering effects" existed in both loess soil columns with and without lids under cyclic diurnal temperature variation [28] . The "soil covering effects" for the soil column with a lid were much more obvious.…”
Section: Introductionmentioning
confidence: 99%